Characterising the specialised metabolism of the wheat Pyrenophora tritici-repentis interaction - Rawlinson, Catherine (Curtin University, 2020)
The necrotrophic fungal pathogen Pyrenophora tritici-repentis (Ptr) causes the economically damaging tan spot disease of wheat. The project investigates the specialised metabolites (SMs) utilised by the pathogen for interaction with the host. This thesis describes the first characterised biosynthetic gene cluster in Ptr, the first report of an amide containing phthalide and the first structurally characterised small molecule necrotrophic effector. Characterisation of host-pathogen holds significant potential in developing control strategies for tan spot disease.